2018
DOI: 10.1387/ijdb.180167ss
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of S-adenosylmethionine decarboxylase impacts polyamine homeostasis during development of Dictyostelium discoideum

Abstract: The polyamines putrescine, spermidine and spermine are essential polycations involved in the regulation of cellular proliferation. They exert dynamic effects on nucleic acids and macromolecular synthesis in vitro but their specific functions in vivo are poorly understood. Here, we have modulated the spermidine levels either by overexpressing the S-adenosylmethionine decarboxylase (samdc) gene or treating the cells with methylglyoxal-bis (guanylhydrazone) (MGBG), an inhibitor of SAMDC. In Dictyostelium, overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In Dictyostelium, overexpression of SAMDC slowed cell proliferation, delayed development and arrested cells in S-phase of the cell cycle. Treatment with MGBG reduced cell proliferation and accelerated development but in samdc OE cells, it increased cell proliferation suggesting critical levels of spermidine to be important (Sharma et al, 2018). In conclusion, they showed that a narrow range of spermidine levels must be maintained for proper growth and development in Dictyostelium.…”
Section: Multicellular Development and Morphogenesismentioning
confidence: 92%
“…In Dictyostelium, overexpression of SAMDC slowed cell proliferation, delayed development and arrested cells in S-phase of the cell cycle. Treatment with MGBG reduced cell proliferation and accelerated development but in samdc OE cells, it increased cell proliferation suggesting critical levels of spermidine to be important (Sharma et al, 2018). In conclusion, they showed that a narrow range of spermidine levels must be maintained for proper growth and development in Dictyostelium.…”
Section: Multicellular Development and Morphogenesismentioning
confidence: 92%
“…[48] Many methods can be applied to prepare chemically crosslinked hydrogels such as chemical cross-linking, chemical and radiation grafting, radical polymerization, condensation reaction, enzyme reaction, and high-energy radiation. [49,50] Small molecular hydrogels, also known as supramolecular hydrogels, are composed of low molecular weight gelator with less than 2000 Daltons, including nucleic acid derivatives, amino acids, small peptides, carbohydrates, and so forth. Compared to polymer hydrogels, small molecular hydrogels have better biodegradability and biocompatibility, and because of the convenience of design and fabrication, they are attracting increasing attention in the field of drug delivery and cancer therapy.…”
Section:  Hydrogelmentioning
confidence: 99%
“…Many of these antiaging properties have been associated with spermidine's potency to exhibit proteostasis on the activation of cytoprotective macroautophagy [13,14]. A recent report showed that endogenous spermidine's genetic modulation affects growth and development in Dictyostelium discoideum [15]. Spermidine levels can be augmented in model organisms and humans when supplemented in food or water [8]; therefore, the impact of polyamines on aging is comparatively feasible to study.…”
Section: Clinical Medicine Hypothesismentioning
confidence: 99%